Photocatalytic removal of cyclohexane on visible light-driven gallium oxide/carbon nitride composites prepared by impregnation - Shu, Chin Lee (2015)
Carbon nitride is a material of interest for photocatalytic reactions due to its catalytic and visible light absorption properties. However, its photocatalytic activity is still low. Hence, modifications must be carried out to improve the photocatalytic activity of carbon nitride. In this work, a series of gallium oxide/carbon nitride composites with various gallium to carbon ratios (Ga/C = 1-50 mol%) was prepared by impregnation method for removal of cyclohexane under visible light irradiation for the first time. The successful preparation of gallium oxide/carbon nitride composites was supported by several characterization techniques. Xray diffraction (XRD) patterns and diffuse reflectance UV-visible (DR UV-vis) spectra revealed that the increased Ga/C ratio resulted in the increased formation of Ga2O3. Furthermore, all the prepared composite samples also showed visible light absorption up to about 430 nm. In the photocatalytic removal of cyclohexane under 6 h of visible light irradiation, sample with low loading of 1 mol% Ga/C improved the photocatalytic activity of carbon nitride for two times. The high activity obtained on the gallium oxide (1 mol%)/carbon nitride composite clearly suggested the presence of synergic effect between small amount of gallium oxide and carbon nitride when they were combined. This study showed that a visible light-driven gallium oxide/carbon nitride composite could be prepared by impregnating a small amount of gallium oxide on carbon nitride and the composite is a potential photocatalyst for removal of cyclohexane under visible light irradiation.